A review on catalytic pyrolysis of microalgae to high-quality bio-oil with low oxygeneous and nitrogenous compounds. (July 2019) - Li, Fanghua; Srivatsa, Srikanth Chakravartula; Bhattacharya, Sankar
Abstract: This paper presents an in-depth review of recent research on catalytic pyrolysis of microalgae and suitable approaches for bio-oil upgrading. The performance of three types of catalysts commonly used in pyrolysis, particularly focusing on microalgae pyrolysis are examined and compared. Also, two deoxygenation methods of catalytic pyrolysis and hydrodeoxygenation and two denitrogenation methods of adsorptive denitrogenation and hydrodenitrogenation for microalgae bio-oil upgrading are reviewed. It is evident that metal-loaded zeolites, particularly loaded with Ni and Pd, are the most favourable catalysts for the reduction of oxygen compounds and partial reduction of nitrogenous compounds from the microalgae bio-oil. Alternative methods for nitrogen removal are necessary for the application of microalgae pyrolysis bio-oils. Adsorptive denitrogenation is found to be the method of interest for dealing with the major nitrogen-containing compounds. The potential adsorbents used for denitrogenation include activated carbon, activated alumina and metal-exchanged zeolites; these all can effectively remove the nitrogen-containing compounds. Besides, all of them can be regenerated by solvent washing or thermal treatment up to five times. A multi-step process with the initial step of devolatilization and followed by catalysis and adsorption is necessary for the best removal of oxygeneous and nitrogenous compounds simultaneously from microalgae bio-oil. Though, there are some challenges in production of high-quality bio-oil from catalytic pyrolysis of microalgae, these processes are of interest for application on commercial scale. Further research and development are still required to maximize the yield and improve the quality of bio-oil from fast and catalytic pyrolysis of microalgae. Graphical abstract: fx1 Highlights: Catalytic pyrolysis of microalgae to high-quality bio-oil reviewed. A multi-situ process of devolatilization, catalysis and adsorption. Effects of different catalysts in heteroatom removal summarized. Metal-loaded on zeolite contribute to high hydrocarbon production. Adsorptive denitrogenation for nitrogen removal from microalgae bio-oil reviewed.